Local Culinary Travel Pattern Development Model in Lerep Tourism Village, Semarang Regency - Jannah, Desika Nur; Arvianto, Bram (Institut Pariwisata Trisakti, 2022)
Culinary tourism activities focus on finding food topics that have never been known or repeating the activity of enjoying the food. Satisfaction for culinary connoisseurs requires a pattern that regulates travel activities to enjoy local food with a tourism approach in the form of narratives, creative content, living culture, and using the power of culture as an icon of culinary tourism destinations. This study aimed to obtain a model for developing Local Culinary Travel Patterns in mapping the foodie tourist market segment and local food production in Lerep Village, Semarang Regency. The research method used in this research is exploratory-descriptive qualitative, exploring the potential of culinary tourism in Lerep Village. The findings showed that creating a local culinary travel pattern model provides a view for tourism actors and prospective tourists to determine tourist activities, especially the local culinary world with strong regional cultural characteristics. This model is also a guideline for tourism village managers with a regional culture with culinary specialization, which is appointed as brand awareness to elevate the identity of the tourist village with traditional culinary icons. Keywords: Culinary Tour, Local Culinary, Travel Pattern